A Miniature 3D Printed On-Off Linear Pneumatic Actuator and Its Demonstration into a Cartoon Character of a Hopping Lamp - Christian L. Nall; Pranav A. Bhounsule (Actuators, 2019)
Although 3D printing has been extensively used to create passive machines and mechanisms, 3D printing of actuators is a relatively new concept. 3D printing of actuators allows greater customization, accelerates the design and development, and consequently saves time and money. We present the design and fabrication of a 3D printed, miniature size, double-acting, On-Off type, linear pneumatic actuator. The actuator has an overall length of 8 cm, a bore size of 1.5 cm, and a stroke length of 2.0 cm. The overall weight is 12 gm and it generates a peak output power of 2 W when operating at an input air pressure of 40 psi ( <semantics> 275.79 </semantics> kPa). This paper demonstrates novel methods to solve the challenges that arise during fabrication that include: (1) chemical post-processing to achieve airtight sealing and a smooth surface finish, (2) strategic placement of a metallic part within 3D printed plastic for higher strength, (3) design of an airtight seal between the cylinder and piston head, (4) chemical bonding of printed parts using adhesive, and (5) use of a lubricant to reduce friction and improve force generation. The power-to-weight ratio of our actuator is comparable to that of high-end commercial actuators of similar size. The utility of the actuator is demonstrated in a series of jumping experiments with the actuator and by incorporating the actuator into a hopping robot inspired by Disney/Pixar Luxo lamp. We conclude that 3D printed pneumatic actuators combine the high power of pneumatics with the low weight of plastics, and structural strength through the selective placement of metal parts, thus offering a promising actuator for robotic applications.